AN EFFICIENT COMBINED CONGESTION HANDLING=--A--cN-:cD~- ROUTE MAINTENANCE PROTOCOL FOR DYNAMIC ENVIRONMENT IN BLUETOOTH NETWORK - TAHIR, TAHIR (2013)
Bluetooth IS a widespread technology for small wireless networks that permits Bluetooth devices to construct a multi-hop network called a scatternet. A large number of connections passing through a single master/ bridge device may create the problem of congestion in a Bluetooth scatternet. In addition, routing in a multi-hop dynamic Bluetooth network, where a number of masters and bridges exist, sometimes creates technical hitches in a scatternet. It has been observed that frequent link disconnections and a new route construction consume more system resources that ultimately degrade the performance of the whole network. As, Bluetooth specification has defined piconet configuration, scatternet configuration has still not been standardized. The main objective of this thesis is to provide an efficient combined protocol for scatternet congestion handling and route maintenance. The methodology contains three parts.